Performance Evaluation of Public and Private Sector Banks in India: A Comparative Study - Maheswari, P (Journal of Commerce and Trade, 2012)
This research paper examines the financial performance evaluation of banking companies in India to examine and to understand how capital adequacy, assets quality, management efficiency, earning quality and liquidity position of banks plays a crucial role in the growth. The present study is mainly based on secondary data. The study concentrates on Indian Banking Industry. Thus the five public sector banks and five private sector banks are selected. The period of the study was ten years from 1999-2000 to 2008-09. Descriptive analysis of average score analysis and the measures of dispersion of Standard deviation and its coefficient of variation is used to evaluate the performance of select banks. Discriminant Function Analysis is used to find out how do Public sector bank differ from Private sector bank in the factors on influencing the profitability. This study which is principally aimed at the financial performance of select public sector and private sector banks in India has examined thoroughly with all the objectives formulated. The entire hypotheses proposed in this study have been examined with appropriate tools also. Based on the studies done in the sample public sector banks and private sector banks, they have to take all the efforts needed to stabilize their financial performances. The study shows, the top ranked bank among the Public sector banks is Bank of Baroda, which has undergone a significant facelift in recent years. Among the select private sector banks, the top ranked banks are KMB and HDFC.